La presunción de inocencia en los procesos administrativos de la policía nacional, por la comisión de una infracción penal - Haro, Luis F. (2020)
This study is important because it will establish whether the guarantee of the presumption of innocence is violated when processing and resolving in the internal affairs units of the National Police, the administrative summaries for alleged disciplinary offenses that lead to the separation of the institution of police servants, for the alleged commission of criminal offenses, the latter being the exclusive competence of the jurisdictional function (criminal guarantee courts), and that, however, after the prosecution of criminal proceedings, many or several of they had ratified their state of innocence, being in this sense the resolution of separation contrary to the constitutional principle under study.